Knowledge and Perceptions of Ternate's Young Generation About Ternate Oral Literature - Alhadar, Fachmi; Rudi S. Tawari; Nurfani (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2024)
This article aimed to discuss the knowledge and perceptions of the young generation in Ternate regarding Ternate oral literature. In practice, oral literature has been eroded so that its values and wisdom are not internalized by the younger generation. For this reason, by using descriptive qualitative methods, this research will reveal the attitudes, knowledge and views of the younger generation regarding the existence of Ternate oral literature. The results of this research show that generally, the younger generation lacks of knowledge of Ternate oral literature. Meanwhile perceptions of value, the younger generation tends to be confused between value and function. This ambiguity in understanding shows that Ternate's oral literature is worrying for the younger generation because they are the successors of this culture.  Nevertheless, all the young people interviewed admitted that they strongly agreed that oral literature must be preserved. This fact shows that the enthusiasm to continue to maintain oral literature does not correlate with knowledge and understanding of the value of Ternate oral literature. Perceptions about the importance of maintaining oral literature are not directly proportional to knowledge of Ternate oral literature.